Emotional intelligence, the ability to access or generate feelings - Brînzea, Nicolae (Technium Social Sciences Journal, 2022)
Emotional control has always been the key to the success of the human person in the daily struggle with stressors of all kinds. Technical and intellectual skills are subject to emotional control, control that can create, based on emotions, successful interpersonal relationships, with beneficial effects that extend from the personal level and extend to the planetary level. These effects define emotional intelligence as superior to intellectual intelligence, which often influences thinking.